Design, synthesis and in vitro and in vivo biological evaluation of flurbiprofen amides as new fatty acid amide hydrolase/cyclooxygenase-2 dual inhibitory potential analgesic agents. (1st January 2021) - Deplano, Alessandro; Karlsson, Jessica; Moraca, Federica; Svensson, Mona; Cristiano, Claudia; Morgillo, Carmine Marco; Fowler, Christopher J.; Russo, Roberto; Catalanotti, Bruno; Onnis, Valentina
Abstract: Compounds combining dual inhibitory action against FAAH and cyclooxygenase (COX) may be potentially useful analgesics. Here, we describe a novel flurbiprofen analogue, N-(3-bromopyridin-2-yl)-2-(2-fluoro-(1, 1'-biphenyl)-4-yl)propanamide (Flu-AM4 ). The compound is a competitive, reversible inhibitor of FAAH with a Ki value of 13 nM and which inhibits COX activity in a substrate-selective manner. Molecular modelling suggested that Flu-AM4 optimally fits a hydrophobic pocket in the ACB region of FAAH, and binds to COX-2 similarly to flurbiprofen. In vivo studies indicated that at a dose of 10 mg/kg, Flu-AM4 was active in models of prolonged (formalin) and neuropathic (chronic constriction injury) pain and reduced the spinal expression of iNOS, COX-2, and NFκB in the neuropathic model. Thus, the present study identifies Flu-AM4 as a dual-action FAAH/substrate-selective COX inhibitor with anti-inflammatory and analgesic activity in animal pain models. These findings underscore the potential usefulness of such dual-action compounds. Graphical Abstract: